PATHOGENETIC SUBSTANTIATION FOR THE ACNE LOCAL TREATMENT IN ADOLESCENT - L.P. Mazitova; L.K. Aslamazyan; L.L. Kvarchakhiya; L.S. Namazova (Union of pediatricians of Russia, 2008)
The authors review the pathogenesis of the come done and its treatment methods. They provide the data on the high effectiveness of the combined therapy by the topical medications: adapalene and benzoyl peroxide in the event of come done among the teenagers.Key words: acne, local treatment, children.